A new annual summer forage crop: Cowpea - Ayan I.; Can M.; Arslan S.; Acar Z.; Mut H. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Four cowpea genotypes (YBS1, YBS2, YBS3, YBS4), were evaluated for forage yield and related parameters at two locations (Samsun and Suluova) in Turkey during 2011 summer growing season. The effects of genotype, location and GxL interaction on 50% flowering stage, fresh and dry forage yield were significant. Average value of the 50 % flowering period and dry forage yield were 49 days and 688 kg/da over the locations and genotypes. The period of 50% flowering among genotypes was longer, however, forage yield was higher at Suluova than Samsun. The highest dry and forage yield was obtained from genotype YBS3 which is also latest in flowering at both locations.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)